Corrosion resistance of nonstoichiometric gadolinium zirconate coatings against CaO-MgO-Al2O3-SiO2 silicate. Issue 6 (June 2021) - Zhang, Chengguan; Fan, Yun; Zhao, Juanli; Chen, Hongfei; Sun, Luchao; Yang, Guang; Liu, Bin
Abstract: Gadolinium zirconate is a promising next-generation thermal barrier coating material and its CaO-MgO-Al2 O3 -SiO2 (CMAS) resistance needs to be further increased. In this study, three gadolinium zirconate coatings with different Gd/Zr ratios are successfully prepared via atmospheric plasma spray using amorphous feedstock. Their mechanical properties and corrosion resistance are investigated. The Young's moduli and hardness of as-sprayed coatings are comparable with the gadolinium zirconate coatings reported in previous literature. Furthermore, the higher Gd content promotes the formation of the Gd-apatite and the depletion rate of CMAS corrosion. As a result, the infiltration depth of Gd2.3 Zr1.7 O6.85 coating after 24 h annealing decreases up to 35 % compared with those of Gd2.0 Zr2.0 O7.0 and Gd1.8 Zr2.2 O7.1, exhibiting an enhanced long-term corrosion resistance. This work develops a viable fabrication method to produce non-stoichiometric gadolinium zirconate coatings with tailorable CMAS corrosion resistance and is expected to promote the future design of thermal barrier coatings with long service life.